Mesenchymal stem cell immunomodulation: In pursuit of controlling COVID-19 related cytokine storm. (7th March 2021) - Song, Na; Wakimoto, Hiroaki; Rossignoli, Filippo; Bhere, Deepak; Ciccocioppo, Rachele; Chen, Kok-Siong; Khalsa, Jasneet Kaur; Mastrolia, Ilenia; Samarelli, Anna Valeria; Dominici, Massimo; Shah, Khalid
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has grown to be a global public health crisis with no safe and effective treatments available yet. Recent findings suggest that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the coronavirus pathogen that causes COVID-19, could elicit a cytokine storm that drives edema, dysfunction of the airway exchange, and acute respiratory distress syndrome in the lung, followed by acute cardiac injury and thromboembolic events leading to multiorgan failure and death. Mesenchymal stem cells (MSCs), owing to their powerful immunomodulatory abilities, have the potential to attenuate the cytokine storm and have therefore been proposed as a potential therapeutic approach for which several clinical trials are underway. Given that intravenous infusion of MSCs results in a significant trapping in the lung, MSC therapy could directly mitigate inflammation, protect alveolar epithelial cells, and reverse lung dysfunction by normalizing the pulmonary microenvironment and preventing pulmonary fibrosis. In this review, we present an overview and perspectives of the SARS-CoV-2 induced inflammatory dysfunction and the potential of MSC immunomodulation for the prevention and treatment of COVID-19 related pulmonary disease. Abstract : Potential mechanism of MSC action in COVID-19 infected patients. SARS-CoV-2 enters cells through receptor-mediated endocytosis via interactions with cell surface protein angiotensin-converting enzyme II (ACE2) receptor with the assistance of transmembrane protease serine 2 (TMPRSS2) protease, thus triggering a complex immune response involved in T cells, dendritic cells, natural killer cells and macrophages. Engineering MSCs with immunomodulatory molecules enhance the efficacy of homing to damaged tissues or cells and attenuate the cytokine storm, ultimately improving patients' outcome.